Aplikasi Penjualan Tiket Seminar Kesehatan Berbasis Web - Uro Abdurohim; Dani Pradana Kartaputra; Fari Ashari (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2021)
Medinar.id is a platform that provides information on the schedules and ticket sales for medical seminars. The website was created to address the challenges previously faced by its owner in finding information about health seminars, purchasing seminar tickets, and distributing health seminar announcements. With the development of Medinar, participants from outside the region can now easily access information about local seminars, focusing specifically on the sale of medical seminar tickets. These tickets are exclusively targeted at healthcare professionals, including doctors, nurses, pharmacists, and midwives. Medinar offers various features, including certificate generation, ticket printing, attendance tracking, and journal upload processes, providing a comprehensive solution for managing medical seminar events.